Pengaturan Penundaan Pemilihan Umum: Urgensi dan Materi Muatannya - Jamaludin Ghafur (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The Indonesian constitution stipulates that elections will be held every 5 (five) years. Regular general elections are a must in a democratic country so that the national leadership succession can take place on an ongoing basis. However, in certain situations such as civil, military, war, or natural and non-natural disasters, it is almost certain that all constitutional agendas – including elections – will be affected. When a state experiences an emergency, postponement or even cancellation of elections is almost certain to occur. Unfortunately, laws and regulations have not at all anticipated the possibility of postponing elections so this has the potential to cause various constitutional problems – one of which is a power vacuum.